Badanie efektywności rynku opcji na Giełdzie Papierów Wartościowych w Warszawie - Majewska, Agnieszka; Majewski, Sebastian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The efficiency of different markets was a subject of researches by plenty of analysts. Most market researches on the derivatives market were concentrated on the valuation, but only a little part of them was concentrated on the market efficiency. The goal of this article is providing an empirical test of efficiency of options quoted on the Warsaw Stock Exchange. The one of approaches of the derivatives' market efficiency testing is researching a relationships between implied and historical volatility. The efficient market hypothesis assumes that volatility prediction, which is build on the sign from market, its named implied volatility, could be estimator of empirical volatility in the future, named historical volatility. Using standard procedures for estimating regression line by the OLS and for verification of econometric models, researcher could conclude about rejection or the lack of bases' disallowable the hypotheses' about market efficiency.The second approach consists in compression the actual warrants prices and the estimated prices generated from Black-Scholes pricing model. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 11-18